Macroeconomic impact of tax changes: The case of Greece from 1974 to 2018 - Panagiotis Asimakopoulos (Economics and Econometrics Research Institute (EERI), 2025)
We adopted an empirical approach to capture the macroeconomic impact of tax changes for the examined period from 1974 to 2018. It is generally accepted that vector autoregression model (VAR) has proven useful for describing the dynamic interrelationships of multivariate series. Our empirical analysis focus on VAR models and Vector Error Correction Models to capture long term relationships Firstly, we apply a VAR (1,1) estimation that shows that the tax rate negatively affects GDP growth in the short run. The regression shows that a one percent increase in the tax rate lowers the level of GDP growth by 0,86%. The effects of a permanent change are given by the cumulative impulse response function which suggest 0,0025 decline of future GDP growth to one-unit upward shift in total tax rates. In addition, we estimate vector autoregressive model 2, VAR (1,1), and examine the short run relationship among real GDP growth, personal income taxes, tax on goods and services, property taxes, debt, general government consumption expenditure, gross fixed capital formation and household consumption. The analysis of the coefficients suggests that income taxes were the most important factor in debt servicing, which had a negative impact on growth, and taxes on goods and services (transaction taxes) served mainly to address difficulties in government spending. Increased government spending and household consumption have a negative effect on growth and investment, while property taxes are positively correlated with investment in fixed assets. Government spending is negatively correlated with gross fixed capital formation. Moreover, we estimate vector autoregressive model 3, as VAR (1,1) and examine the short run relationship among real GDP growth, debt, general government consumption expenditure and tax rates. Our estimation result suggests that debt, government spending and the level of taxation are negatively correlated with GDP growth while lagged GDP growth is positively correlated with GDP growth of current period. In this context, we conclude that policymakers should pursue a strategy that promotes the rationalization of government spending and the sustainability of debt, keeping the revenue capacity at a level that does not harm long-term growth.
Keywords: E6; H2; 330; VAR; VECM; Macroeconomic Impact; Tax Revenues; Greek Tax